Implementation of Toriduino (Toricelli Berbasis Arduino) as a Physics Learning Media in XI IPA SMA Negeri 15 Bandung - Andi Fauziah; Dilmatin Nuraeni; Widia Linta Nurjanah; Dadi Rusdiana (Proceeding International Conference on Religion, Science and Education, 2023)
The development of learning media has been carried out based on the results of interviews with physics teachers who stated that schools still experience limitations in the manufacture, use of learning media and the physics learning outcomes of students on the concept of dynamic fluid which is still relatively low. This development aims to produce Toriduino (Arduino-based Toricelli) learning media on dynamic fluid material Toricelli sub chapter. This research uses the Research and Development method using the ADDIE model. At the Analysis stage, a needs analysis is carried out, the Design stage is carried out designing arduino-based learning media using a flowmeter sensor as a tool to measure the discharge of water that comes out in the toricelli experiment, the Development stage is carried out making learning media products and also testing tools, the Implementation stage of Toriduino teaching media is carried out at SMA 15 Bandung with a sample of 30 students, and the last stage Evaluation is carried out analyzing the results of the implementation which results in recommendations for Toriduino learning media. Research data collection was carried out using worksheet, response questionnaires to find out the response of students to the Toriduino, interviews were conducted to further analyze the results of the worksheet and questionnaire analysis. Analysis of the majority of learner response questionnaires showed positive responses, with student responses strongly agreeing and agreeing, with 50% and 40% stating that Toriduino learning media worked well. I was. Toriduino helps students understand the concept of dynamic fluids. 33% completely agree and 40% agree with Torricelli's sub chapter. The results of the worksheet analysis, survey responses, and interviews, it was concluded that Toriduino Media still has some shortcomings and needs further development. Specifically, improve the worksheet instructions and complete the Arduino programming to read the output unit m/s.